Sociodemographic Factors Toward Stunting: A Community Based Cross Sectional Study - Agustini, Rahma Dewi; Z, Sri Nurlaily; Taidi, Jein Eka Wirahmi; Nurhidayah, Nurhidayah; Rasyid, Puspita Sukmawaty (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2023)
Stunting is a malnutrition problem that occurs globally and has long-term impacts on both health and cognitive. There have been no studies related to sociodemographic factors towards stunting in one of the areas with the most stunting rates in Gorontalo. This study aims to provide an overview of the prevalence of stunting and associated factors. This research method is descriptive with a cross-sectional approach in 325 children aged 6-59 months, in 8 villages in Tilango District, Gorontalo Regency. Mothers who met the criteria and came to the posyandu sequentially (consecutive sampling) were given a questionnaire. The prevalence of stunting is 116 (35.7%). Mothers who give birth to children with Birth Length (OR=3.65; 95% CI: 2.261-5.88), Birth Weight (OR:7.3; 95% CI:  3.774-14.238), Exclusive Breastfeeding (OR=3.586; 95% CI: 2.217-5.799, and Complementary Foods (OR=3.586; 95% CI: 2.217-5.799) associating against stunting. The conclusion of this study is that the prevalence of stunting in the Tilango District area is still very high, but only four of the 12 sociodemographic factors studied are associated with stunting. Nutritional status screening, monitoring of weight gain during pregnancy, as well as regular ANC examinations are important for Midwives and pregnant women at every contact, especially in first-level health facilities.